2020
DOI: 10.1016/j.bbagen.2019.129440
|View full text |Cite
|
Sign up to set email alerts
|

SLMP53-1 interacts with wild-type and mutant p53 DNA-binding domain and reactivates multiple hotspot mutations

Abstract: Background: Half of human cancers harbour TP53 mutations that render p53 inactive as a tumor suppressor. As such, reactivation of mutant (mut)p53 through restoration of wild-type (wt)-like function represents one of the most promising therapeutic strategies in cancer treatment. Recently, we have reported the (S)-tryptophanolderived oxazoloisoindolinone SLMP53-1 as a new reactivator of wt and mutp53 R280K with in vitro and in vivo p53-dependent antitumor activity. The present work aimed a mechanistic elucidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…This finding was consistent with results obtained recently with compound 1 in cancer cell lines with mutated p53. In these cell lines, compound 1 was shown to activate wt p53 and restore wt‐like function to mutp53 R280 K by directly binding to this protein [42] …”
Section: Resultsmentioning
confidence: 99%
“…This finding was consistent with results obtained recently with compound 1 in cancer cell lines with mutated p53. In these cell lines, compound 1 was shown to activate wt p53 and restore wt‐like function to mutp53 R280 K by directly binding to this protein [42] …”
Section: Resultsmentioning
confidence: 99%
“…Transient transfection of mutp53 in human H1299 tumor cells For ectopic expression of mutp53, p53 null H1299 cells were transfected with 75 ng of pcDNA3 mammalian expression vectors encoding full-length human mutp53 (R280K, R175H, G245D, G245S, R248Q, R248W, R273H, R273C, Y220C or R282W), or empty pcDNA3, as described (Gomes et al, 2020).…”
Section: Cell Viability and Proliferation Assaysmentioning
confidence: 99%
“…The starting structure for the modeling was the crystal of wtp53 DBD tetramer bound to a DNA target (2AC0) (Kitayner et al, 2006), as described in a previous work (#94) (Gomes et al, 2020). The R248W mutation was performed using Chimera swapaa tool and then geometry optimized with the Amber18/ parm99SB (#100) (Hornak et al, 2006).…”
Section: Modelingmentioning
confidence: 99%
“…In earlier studies, SLMP53-1 was identified as a new activator of wt-and mutp53, with encouraging in vitro and in vivo p53-dependent antitumor activity [24,27]. Data from SwissADME analysis [25] also showed that SLMP53-1 followed criteria for drug-likeness, gastrointestinal adsorption, lipophilicity, and solubility (Supplementary Tables S1-S7).…”
Section: Discussionmentioning
confidence: 93%